Bortezomib, melphalan, and prednisone in elderly patients with relapsed/refractory multiple myeloma1. Issue 5 (23rd October 2012) - Petrucci, Maria Teresa; Levi, Anna; Bringhen, Sara; Scotti, Simona; Gentilini, Fabiana; Russo, Simone; Siniscalchi, Agostina; Larocca, Alessandra; Grammatico, Sara; Boccadoro, Mario; Foà, Robin; Palumbo, Antonio
Abstract BACKGROUND: In elderly patients with newly diagnosed multiple myeloma (MM), the addition of bortezomib to standard, combined oral melphalan and prednisone (MP) significantly increases the response rate and event‐free survival compared with MP alone. METHODS: In this phase 1/2 trial, the authors assessed the dosing, efficacy, and safety of a lower dose‐intensity MP schedule plus weekly bortezomib as salvage treatment for elderly patients with MM. To assess the maximum tolerated dose, 19 patients who had relapsed/refractory MM after 1 or 2 lines of treatment entered the first phase of the study. They received melphalan at a dose of 24 mg for 28 days; bortezomib 1.3 mg/m2 on days 1, 8, 15, and 22; and prednisone at a dose of 50 mg every other day of a 28‐day cycle for a total of 9 cycles. At the end of the first phase, based on the good efficacy and acceptable toxicity of this combination, an additional 23 patients were enrolled. RESULTS: After a median follow‐up of 21 months, of 42 patients who relapsed, 24 (57%) obtained at least a partial response, 4 had stable disease, and 11 had progressive disease. The median time to progression was 18 months, and the median overall survival was 30 months. Grade 3 and 4 toxicity was observed in 16 of 42 patients (38%) and was more frequent during the early cycles. CONCLUSIONS: A weekly infusion of bortezomib associated with lower dose‐intensity MP induced a high proportion of responses and was well tolerated in elderly patients with relapsed/refractory MM. Cancer 2013. © 2012 American Cancer Society.